Theorizing the lesbian hashtag: Identity, community, and the technological imperative to name the sexual self. Issue 3 (3rd July 2018) - Herrera, Andrea P.
ABSTRACT: This analysis integrates poststructuralist and symbolic interactionist approaches to the self by incorporating the insights of science and technology studies regarding categorization processes. While the advent of the Internet has freed many individuals from geographical constraints on community formation, the architectures of online platforms produce a technological imperative to name aspects of the self with words. Using sexual identity hashtags on Instagram (e.g., #lesbian) thus performs paradoxical functions: the hashtag both enables the construction of a sexual identity within an affirming community and also reinforces the power relations that compel individuals to name and account for their sexual selves. By illustrating one way sexual identities function in the online lives of young women, this research complicates other scholars' findings that the salience of sexual identity categories is decreasing.